Inventory of orchids plants (Orchidaceae) in the Tangkahan area, Langkat Regency, North Sumatra - Ramadhan, Dita Alviana; Sarjani, Tri Mustika; Suwardi, Adi Bejo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia is a mega biodiversity country with great biodiversity abundant as flora and fauna. One of the plants that contributes in the richness of flora in Indonesia, namely orchids. Orchids are a group of plants belonging to the Orchidaceae family. The purpose of this research is to find out the types of the Orchidaceaefamily and find out characteristics of the orchidaceae family. This research was conducted in May 2024 in the Tangkahan area, Namo Sialang village, Langkat Regency, North Sumatera. This research was conducted using an exploratory method (exploration) by directly observing the orchids at the research location. Sampling was carried out by purposive sampling. Data analysis carried out by describing the spescies obtained based on morphology, identified, and made a key to the determinationpresented in form tables and figures. Based on the results of research on orchids types (Orchidaceae) which is found in the Tangkahan area, Langkat regency, North Sumatera as many as 13 species belonging to 10 genera, namely Acriopsis liliifolia, Archnis flos-aeris, Cattleya intermedia, Cymbidium finlaysonianum, Dendrobium aphyllum, Dendrobium cretaceum, Dendrobium crumenatum, Epidendrum rigidum, Phalaenopsis amabilis, Phalaenopsis equestris, Spathoglottis plicata, Trimezia martinicensis, and Vanda tricolor. Every speies of orchid found to have different characteristics ranging from stems, leaves, flowers, and their living habitat.